2021
DOI: 10.3389/fcell.2021.647387
|View full text |Cite
|
Sign up to set email alerts
|

LMO7 as an Unrecognized Factor Promoting Pancreatic Cancer Progression and Metastasis

Abstract: Pancreatic cancer (PC) is one of the most lethal human malignancies without effective treatment. In an effort to discover key genes and molecular pathways underlying PC growth, we have identified LIM domain only 7 (LMO7) as an under-investigated molecule, which highly expresses in primary and metastatic human and mouse PC with the potential of impacting PC tumorigenesis and metastasis. Using genetic methods with siRNA, shRNA, and CRISPR-Cas9, we have successfully generated stable mouse PC cells with LMO7 knock… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…In contrast, FBXO20 could facilitate the migration ability of breast cancer cells in a cell-specific manner via modulating Rho-MRTF-SRF signaling ( 14 ). Liu et al verified that the expression levels of FBXO20 mRNA and protein were increased in mouse and human pancreatic cancer tissues ( 16 ). The results of Liu were consistent with our findings in multiple public databases to some extent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, FBXO20 could facilitate the migration ability of breast cancer cells in a cell-specific manner via modulating Rho-MRTF-SRF signaling ( 14 ). Liu et al verified that the expression levels of FBXO20 mRNA and protein were increased in mouse and human pancreatic cancer tissues ( 16 ). The results of Liu were consistent with our findings in multiple public databases to some extent.…”
Section: Discussionmentioning
confidence: 99%
“…FBXO20, also known as LIM (Lin11, Isl-1, and Mec-3) domain 7 (LMO7), belongs to PDZ and the LIM domain-containing protein family. It has been reported that LMO7 played a role in the regulation of cell adhesion, mitosis, and cancer metastasis and progression, including breast cancer, lung adenocarcinoma, and pancreatic cancer (13)(14)(15)(16). Clinically, some FBXO family members were closely linked to the overall survival (OS) and disease-free survival (DFS) of patients with breast cancer (17).…”
Section: Introductionmentioning
confidence: 99%
“…CXCR3-A and CXCR3-B are the best studied isoforms and differ in their 3′ splice site on exon 2, which are 245 bp apart. CXCR3-B uses a more proximal 3′ splice site than CXCR3-A, which results in a longer extracellular N-terminus [ 1 , 2 ] ( Figure 1 ). Notably, CXCR3-B uses a more downstream start codon.…”
Section: Introductionmentioning
confidence: 99%
“…Immune cells have been shown to mainly express CXCR3-A, with low levels of CXCR3-B co-expression [ 2 , 4 ]. In contrast, endothelial cells and pericytes only express CXCR3-B [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding its intracellular distribution, the LMO7 protein can be found in the nucleus, perinuclear region, cytoplasm and/or on cell surface, particularly in cell–cell adhesions (where it can interact with nectin and E-cadherin through afadin and alpha-actinin) and focal adhesions [ 2 , 8 , 9 , 10 ]. Importantly, misregulation of the PDZ–LIM proteins is involved in cancer [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%